The effect of additional therapy of Curcuma longa and Boswellia serrata on NSAIDs on functional activity in osteoarthritis patients - Rizaldy Taslim Pinzon; Jessica Herwanto (Farmasains : Jurnal Farmasi dan Ilmu Kesehatan, 2020)
Osteoarthritis (OA) is a chronic disease that causes joint pain, stiffness, and swelling. The knee is the most affected joint in osteoarthritis. A typical therapy that often used for osteoarthritis patients is NSAIDs, but a previous study showed that satisfactory pain control could not be achieved with NSAIDs alone, so that additional analgesic therapy is needed. Some previous studies showed the extracts of Curcuma longa and Boswellia serrata were promising in reducing pain and do not cause serious side effects in osteoarthritis patients. This research aims to measure the effect of additional therapy Curcuma longa and Boswellia serrata to NSAIDs on functional activities in knee osteoarthritis patients. The type of this research is cross-sectional, involving 71 patients. This study uses secondary data taken from previous RCT studies by completing questionnaires to determine the WOMAC score of osteoarthritis patients at Bethesda Hospital and Panti Rapih Hospital in Yogyakarta. Data were analyzed statistically using the licensed SPSS program with the Wilcoxon test and the Mann-Whitney test. The reduction of WOMAC scores was superior in the NSAIDs group with Curcuma longa and Boswellia serrata after being given therapy for four weeks but not significant (p = 0.372). The giving of additional therapy Curcuma Longa and Boswellia serrata to NSAIDs is not superior compared to NSAIDs in increasing functional activities in osteoarthritis patients.